Craniopharyngioma arising from fourth ventricle - Jha, Binit Kumar; Jha, Prabhat; Jha, Rajiv; Bista, Prakash (Nepal Journal of Neuroscience, 2020)
Craniopharyngiomas usually involve the sellar and suprasellar space. Very few cases of craniopharyngiomas arising in the posterior fossa without extension to the sellar and suprasellar space have been reported in literature. This case describes a patient with craniopharyngioma confined only to the ventricular system.